Infra-estrutura urbana em bairros residenciais no Sul do Brasil - Hüther, Márcia Cristina (2006)
The present study analyses the urban infra-structure system in residential districts in medium size cities. The areas analysed were the water nets, sewerage, electric energy, urban tree, road system, and the local pluvial drainage system. The cities of Passo Fundo, RS and Lages, SC were selected for this study because of they’re representatives in their own regions, where there aren’t any studies about the subject, the urban infra-structure system. The analysis was done through a case study between districts of different social classes, approaching technical aspects, through a bibliographic review and existing legislation, and quality, where the APO methodology was used (post-occupation valuation), verifying the satisfaction of the users through the questionnaires referring to the existing systems. After this approach was realized a comparative analysis between the districts of each city, later between the cities and their own districts. The research shows the necessity to search better alternatives for the project, managing and maintenance of the urban infra- structure system, searching to qualify the services give for them in each district of different socials classes.